Polysaccharide from Hemerocallis citrina Borani by subcritical water with different temperatures and investigation of its physicochemical properties and antioxidant activity - Ti, Yongrui; Zhang, Yanli; Ban, Yüqian; Wang, Xiaoxiao; Hou, Yüqing; Song, Zihan (Frontiers in Nutrition, 2022)
Hemerocallis citrina Borani as a low-cost vegetable, has various health benefits. However, the industry of H. citrina Borani is in the state of primary processing, with poor economic benefits. This study aimed to investigate the physicochemical properties, and the antioxidant activity of H. citrina Borani polysaccharide (HCBP) using subcritical water extraction (SWE) at different temperatures, to expand the value of H. citrina Borani. HCBP mainly composed of nine monosaccharides (glucose, galactose, rhamnose, fucose, mannose, arabinose, xylose, galacturonic acid and glucuronic acid), among which the content of neutral sugar was higher and uronic acid was lower. HCBP contained glycosidic bond of β-configurations and trace quantities protein. The molecular weight of HCBP decreased with increasing temperature. Shear thinning occurred in HCBP with the increase of shear rate (0.01-1 s−1), and the apparent viscosity of HCBP decreased at higher temperature (150°C-160°C) with the increase continuously of shear rate (1-10 s−1), but almost remained constant at lower temperature (130 °C-140°C). Scanning electron microscope showed that HCBP had rough surface, loose structure, obvious particle gap, and irregular shape. In addition, HCBP extracted at 160°C had strong FRAP activity, and HCBP extracted at 130°C and 140°C had better ABTS radical scavenging activity. This study suggests that HCBP extracted by SWE could provide a cheap raw material as food thickening agent and natural antioxidants.